Breast-feeding: factors leading to precocious weaning in Passo Fundo, RS - Parizotto, Janaína; Zorzi, Nelci Terezinha (O Mundo da Saúde, 2008)
This exploratory-descriptive study with a qualitative approach aimed to identify factors linked to early weaning in Passo Fundo-RS. It was carried out in the Vaccination Room of the local Health Center with mothers with children from zero to six months of age and were in the weaning process. Data were collected from August to September 2006 by means of a semi-structured interview and annotations in a field journal, being interpreted by means of the thematic analysis technique. The interpretation of information collected showed the following themes: Knowledge Deficit /Lack of Information, Mammary Problems / Use of Feeding Bottle, Health Professionals, Special Situations, and Women Out Of Home / Working Women. This study supplies information for promoting the predominance of breast-feeding and stop the practice of early weaning by raising conscience and encouraging breastfeeding.